Pengaruh Penggunaan Media Quizizz terhadap Motivasi Belajar dan Hasil Belajar Siswa dalam Pembelajaran - Urip Adil Wicaksono; Muhammad Yusuf Amin Nugroho; Sri Jumini (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to determine the effect of using the digital-based learning media Quizizz on students’ learning motivation and learning outcomes in Islamic Religious Education (PAI) at SMAN 1 Kaliwiro Wonosobo. The research method employed was a quasi-experimental design with a pretest-posttest control group design. The subjects were 70 eleventh-grade students, consisting of an experimental class (XI-6) and a control class (XI-7). The research instruments included a multiple-choice learning achievement test and a learning motivation questionnaire using a Likert scale. Data were analyzed using the Wilcoxon test, Mann–Whitney test, and simple linear regression analysis. The results showed a significant effect of using Quizizz on students’ learning motivation and learning outcomes. Students in the experimental class demonstrated higher improvements in both motivation and learning outcomes compared to those in the control class. This indicates that the use of Quizizz can create an interactive, enjoyable, and competitive learning atmosphere that enhances students’ enthusiasm for learning.